UPAYA PENINGKATAN PELAYANAN TERHADAP KEPUASAN MAHASISWA BERDASARKAN HASIL ANALISIS METODE SERVQUAL DAN REGRESI LINIER BERGANDA (Studi Kasus Jurusan Teknik Mesin Universitas di Malang) - Sujatmiko Sujatmiko; Purnomo Budi Santoso; Rudy Soenoko; Murti Astuti (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2013)
Recorded approximately 27 universities in this city is increasingly fierce competitive situation from time to time, causing many colleges difficult to increase the number of students [1]. Department of Mechanical Engineering at the University contained in Malang has not identified the quality of service and support strategy for the satisfaction level of students so as to improve the quality of students. In this research use corporation of SERVQUAL method and multiple linear regression to analyze the results of the questionnaire. This processing produces Gap values and linear regression analysis, it can be calculated the value of Servqual that known and will be prioritized for enhanced service quality. Conclusions and recommendations in order to get improved quality of improvement efforts of the priority criteria for enhanced quality service. Based on data processing using multiple linear regression analysis only tangible dimension that significantly to improve overall satisfaction. To prioritize the improvement of his physical condition improved following completion of facilities and infrastructure improvements in the information media (internet), completeness of facilities and infrastructure improvements in the lecture, the addition means supporting information, improved seating and desks Conditions comfortable class, classroom hygiene, completeness of facilities improvement and infrastructure in the library, improvement classroom air circulation, comfortable classroom temperature, comfortable classrooms lighting.